Cell Division of Escherichia coli BUG-6: Effect of Varying the Temperature Used as the Nonpermissive Growth Condition - Reeve, John N. (1972)
When Escherichia coli BUG-6 is shifted from 30 C to 36 or 38 C, division does not stop, but the rate of division of the cell population is initially decreased followed by a period of increased rate of division before the rates characteristic of growth at 36 and 38 C are obtained. After a shift from 30 to 40 C, the rate of cell division gradually decreases over a 10-min period and then stops. The inhibition continues for 25 min, and then the cells divide rapidly before the division rate characteristic of 40 C is obtained. If filaments produced by 45 min of growth at 42 C are temporarily replaced at 30 C and then returned to 42 C, division occurs at 42 C. The amount of division is dependent on the length of the period at 30 C and can be decreased by a 3-min pulse of chloramphenicol immediately before the 42 to 30 C shift.